2016
DOI: 10.1155/2016/8065765
|View full text |Cite
|
Sign up to set email alerts
|

Adult Onset Vitiligo: Multivariate Analysis Suggests the Need for a Thyroid Screening

Abstract: Background. There are limited epidemiological studies evaluating the effect of age at onset on disease features in vitiligo. Objectives. To identify factors associated with adult onset vitiligo in comparison with childhood onset vitiligo. Patients and Methods. We retrospectively collected medical records of 191 patients. Such records included clinical examination, personal and familial medical history, laboratory evaluations, concomitant vitiligo treatment and drug assumption. Results. 123 patients with a dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
(31 reference statements)
1
25
0
1
Order By: Relevance
“…Lazzeri et al (2016) shared similar results in which out of 188 patients with vitiligo, the non-segmental type was more commonly found (94.68%), followed by segmental type (4.26%) and unclassifiable vitiligo (1.06%). 13 Wang et al (2013) conducted a similar study in China with the results which showed that nonsegmental vitiligo is the most common vitiligo found in the community. 14 Another study by Sun et al (2006) and Mchepange et al (2010) also showed similar results.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Lazzeri et al (2016) shared similar results in which out of 188 patients with vitiligo, the non-segmental type was more commonly found (94.68%), followed by segmental type (4.26%) and unclassifiable vitiligo (1.06%). 13 Wang et al (2013) conducted a similar study in China with the results which showed that nonsegmental vitiligo is the most common vitiligo found in the community. 14 Another study by Sun et al (2006) and Mchepange et al (2010) also showed similar results.…”
Section: Discussionsupporting
confidence: 77%
“…A study by Lazzeri et al (2016) had the similar results in which out of 191 patients with vitiligo, late-onset vitiligo was more commonly found (64.40%) compared to early-onset vitiligo (35.60%). 13 Segmental vitiligo is the most common type found in this study (73.44 %). Lazzeri et al (2016) shared similar results in which out of 188 patients with vitiligo, the non-segmental type was more commonly found (94.68%), followed by segmental type (4.26%) and unclassifiable vitiligo (1.06%).…”
Section: Discussionmentioning
confidence: 58%
“…Vitiligo usually precedes thyroid disorders by many years, even decades . The opposite is also reported by some studies . Among the autoimmune thyroid diseases present in vitiligo patients, many studies find hypothyroidism to be the most common .…”
Section: Specific Autoimmune Comorbiditiesmentioning
confidence: 86%
“…14,32 The opposite is also reported by some studies. 25,41 Among the autoimmune thyroid diseases present in vitiligo patients, many studies find hypothyroidism to be the most common. 5,22,25 Another study found Grave's disease to be the most frequent in vitiligo patients.…”
Section: Thyroid Diseasementioning
confidence: 99%
“…Immunological interventions using levamisole, isoprinosine, and topical tacrolimus (Nordal, Guleng, & Rönnevig, ) are also another options. Moreover, surgical methods including full‐thickness punch and split‐thickness grafts, transplant of melanocyte–keratinocyte cultured suspension, and transplantation of pure melanocyte cultured suspension have been performed as well (Hossani‐Madani & Halder, ; Lazzeri, Colucci, Cammi, Dragoni, & Moretti, ; Pasricha & Khera, ; Toossi et al, ).…”
Section: Introductionmentioning
confidence: 99%